Sironi alla prova - La V Triennale: una grande sfida vinta - Longari, Elisabetta (Firenze Architettura, 2019)
The V Edition of the Milan Triennale surely represented for Sironi the best possibility to design a manifestation in its overall physiognomy, according to a coherent and unitary idea of relationship between decoration and architecture, in a connection modulated through the use of different languages and through the declination of multiple variations.